PERAN PENYULUH BAGI PETERNAK DALAM USAHA PETERNAKAN KERBAU DI KECAMATAN MOA KABUPATEN MALUKU BARAT DAYA - Carolina Anaktototy; George S. J. Tomatala; Lily Joris (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2021)
This study aims to examine the role of extension workers for breeders in buffalo farming in Moa District, Southwest Maluku Regency. The method used in this research is survey method, the sample is determined by purposive sampling., The form of qualitative descriptive analysis with the first stage is checking the data, in this activity it is carried out after conducting an interview (filling out a list of questions). Based on the results of the research, the performance of agricultural extension services at the Moa Subdistrict BPP in developing buffalo farming in the research village is running well but not yet optimal. This is because the quantity of extension workers is still small and the quality of the timeliness of extension workers in completing the work is not good because the amount of work to be done is not balanced with the quantity of extension workers. In addition, there is still a lack of infrastructure for extension workers such as the posluhdes (Village Extension Officer).